Kankrej breed: An incredible germplasm of Zebu cattle (Indian Journal of Animal Production and Management, 2016)
The importance of cattle in Hindu mythology, is  well established, even today it is known by different  names viz. Kamdhenu, Kapila, Nandini, Surabhi and  people worship it as “Gau-Mata”, but the fact is that  legendary history of Indian cow breeds from the time  of glorious India to the present day times expedited  that today’s Indian cow breeds need improvised  policy even though Indian bovine breeds were best  in the world, then what actually happened to these  cow breeds. The one important reason might be the  European invaders eyed the invaluable germplasm  of these zebu cattle and “East India Company” started the export of superior quality of zebu cattle  and bulls from India. Indian farmers were misguided  to abscond their cows on the roads by spreading the  air that they yield less milk. Subsequently, Indian  farmers adopted exotic breeds while the foreigners  started rearing zebu cattle.
Keywords: germplasm; Zebu cattle